Implementasi Program Kemitraan dan Program Bina Lingkungan Pada PT. PELINDO III Surabaya: Implementation of the Partnership Program and Community Development Program at PT. PELINDO III Surabaya - Andrianto, Andrianto (Journal of Accounting Science, 2017)
Corporate Social Responsibility Program which has been run by PT. Pelindo III Surabaya, realized in the form of partnership program and environmental development program. Partnership Program is a program launched by the government as a form of awareness and responsibility of State Owned Enterprises (BUMN) to economic development, especially small business in the company environment, while environmental development program is a program that concerns PT. Pelindo III (Persero), which is one of the state-owned enterprises in facing the social conditions of the community around the company. This research is a quantitative descriptive research with case study approach to study and explain about both CSR programs that have been run by PT. Pelindo III (Persero). From the results of research, it can be concluded that both CSR programs that have been run by PT. Pelindo III (Persero) is very good and programmed. This is evidenced by the existence of work programs every year in its implementation accompanied by a report on the position and financial activities of the partnership program and environmental development. So in the preparation of financial information and implementation of the practice both programs have been very fulfilling elements of transparency.